Melacak Nilai-Nilai Budaya Organisasi Islami pada Organisasi Pengelola Zakat (OPS): Telaah Literatur Klasik - Rahmad Hakim (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
The discourse concerning zakâh and its scope have occurred throughout the course of Islamic civilization. It is because zakâh has an important and strategic role in Islam. Furthermore, zakâh is the oldest state’s resources in Islam. Beside as one pillars of religion (arkânu al-Islâm),itsalso as the way to prosper ummah and avoid the poverty. This paper aims to conduct in-depth study related to the cultural values of the organization on zakat management organizations (OPZ) with the study of classical literature in the field of tafsîr and the state finance (al-kharâj, al-amwâl and aḥkâmsulṭâniyyah). Based on study conducted in this research, concluded that: zakâh is an officer who has the duty and authority to manage zakat. Among the criteria of zakâh are as follows: trustworty(âminin), reliable (thiqatin), restraint (‘afîfin), tend to goodness (ṣalâḣ), always in advise (nâṣiḣin), trusting the government and the people (ma’munin ‘alaikawa ‘alâra’iyyatika). Some grades of organizational culture founded in classical literature as follows: being honest, following the sunnah of Rasulullah and caliph after him, does not merge the object of zakâh, be careful in counting, do not bring the zakâh out the territory, does not collect zakâh up to ḥaul, and so forth.